Manajemen Keuangan Pendidikan SD Islam Roudhotul Muttaqin Desa Ngares Wetan Kecamatan Gedeg Kabupaten Mojokerto - Khamidi, Amrozi; Wulandari, Ayu; Amalia, Kaniati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This study aims to determine the extent of financial management and interesting things in improving the quality of learning at SD Islam Roudhotul Muttaqin. Schools have the duty to manage school finances based on the principles of financial management can be utilized optimally. School financial management is based on the principles contained in article 48 of the 2003 Law on the National Education System, namely the principles of justice, efficiency, transparency, and public accountability. This research was conducted using descriptive qualitative methods, direct observation and interviews with related parties, namely the Principal and Treasurer. In managing this finance, SD Islam Roudhotul Muttaqin has agreed to plan, manage, implement, report, and evaluate. Relevant matters related to financial management and learning quality, namely through the collaboration program currently being carried out by SD Islam Roudhotul Muttaqin with other Non-Formal Education Institutions hereby have a positive impact on all parties, teachers, schools, students, and parents.